Thoracic Kidney: Extremely Rare State of Aberrant Kidney - Mahdi Khoshchehreh; Omalbanin Paknejad; Mehrdad Bakhshayesh-Karam; Marzieh Pazoki (Case Reports in Urology)
The thorax is the rarest place among all forms of renal ectopia. We report a rare case of an unacquired thoracic kidney. Only about 200 cases of the thoracic kidney have ever been reported in medical literature worldwide. In this paper we present the rarest form of nontraumatic nonhernia associated, truly ectopic thoracic kidney. The differential diagnosis and management options and classification of this rare form of aberrant kidney are discussed.